Cooper mining tailings substrate in the production of white ipe - Arruda, Anna Gabriela Rocha; Costa, Denilson da Silva; Gomes Tabosa, Louis Dostoievsky; Costa, José Ronaldo Medeiros; Oliveira, Ângelo Kidelman Dantas de; Oliveira, Fernando Kidelmar Dantas de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
One of the main metals explored in the world is copper (Cu), a native element, which is rarely found pure in nature. The mining and processing of copper generates environmental debates due to the generation of polluting agents in the areas of concentration, smelting and refining, in addition to the negative impacts imposed on the vegetation and topography of the mined area. The study aimed to investigate the initial morphometric performance of the white ipe (Tabebuia roseo-alba (Ridl.) Sandwith) in a substrate composed of copper mining tailings and increasing percentages of organic matter, evaluate its phytoremediator potential and the Dickson’s Quality Index (IQD). The experimental design was the entirely randomized one. Morphometric data of the treatment were collected regarding height, stem diameter and number of leaves of the plant species where they were later submitted to statistical and IQD analysis, in addition to calculations related to the index and translocation factor of copper in the plant and its phytoextracting capacity. The phytomass compartmentalized in roots and aerial part was collected, placed in a drying oven, ground and sent to the laboratory for the proper evaluation of the copper metal in the compartments of the plant species, in addition to the chemical evaluation of the substrate. It was concluded that white ipe has the potential to phytostabilize the copper element coming from mining tailings, as well as achieving a satisfactory IQD in treatment composed of 90% of mining tailings and 10% of organic matter.